Prevalence of benign prostatic hyperplasia among obese patients at a tertiary care hospital in Karachi. - Seerat Ul Uroos; Waqas Memon; Sumaiya Noor; Zubda Malik; Muhammad Rashid; Ali Khowaja (International Journal of Endorsing Health Science Research, 2024)
Background: Benign prostatic hyperplasia (BPH) is a prevalent condition in older men, marked by the noncancerous enlargement of the prostate gland. Obesity and various lifestyle factors have been linked to an increased risk of developing BPH, though the exact relationship remains unclear. This study aimed to investigate the frequency of BPH in obese patients and explore the potential association between obesity and BPH, alongside other factors such as smoking, hypertension, and age. Methodology: A cross-sectional study was conducted on 182 male patients aged 45–85 years diagnosed with BPH at the Urology Outpatient Department of a tertiary care hospital between January and February 2024. Body mass index (BMI) was calculated from patients’ height and weight, and all patients underwent transabdominal ultrasound to confirm BPH. Additional demographic and clinical data, including smoking status, hypertension, and diabetes, were recorded. Results: The mean age of participants was 64.45±2.95 years, with all patients classified as obese (Class 1: 33%, Class 2: 33%, Class 3: 34.1%). The majority (72.5%) of participants had BPH, while none were diabetic, 47.8% were hypertensive, and 34.7% were smokers. Statistical analysis revealed no significant association between BPH and obesity (P-value=0.06), smoking (P-value=0.42), hypertension (P-value=0.13), or age (P-value=0.64). Conclusion: This study found no significant association between BPH and obesity, despite the high prevalence of BPH in the obese population. Further longitudinal research is warranted to examine whether targeted obesity management could meaningfully impact BPH progression and treatment outcomes.